Possibilities of using local raw material - black sand for water purification filters (Международный научный журнал «Инженер», 2026)
In this article, in order to create good conditions for the population in Uzbekistan, including the need for drinkingwater: population growth, urbanization, climate change, and other problems, experimental work was carried outon local sand, including black sand. It was stated that this sand filtration device can retain unnecessary substancesin water that are harmful to human health and make water reusable. Methodologically, an attempt was made toachieve a new approach to the problem based on literature analysis, practical analysis, and the formula for thedependence of filtration speed on hydraulic gradient developed by Darcy. Water that leaked from black sand wasanalyzed using a TDS&EC tester and a spectrophotometer. These analyses are presented in tables and diagrams.